PROBLEMATIKA PENYESUAIAN DIRI SISWA DI SEKOLAH MENENGAH ATAS - Bau Ratu (Paedagogia: Jurnal Pendidikan, 2018)
Lately, the weakness of the individual's ability to act effectively and healthily against situations, reality and social relationships, due to low self-esteem, neglect and self-denial if allowed to do so may lead to aggressive behavior, regardless of peer, isolate to psychological problems heavier. Guidance and counseling services have a strategic role in improving students' social adjustment. Some good approaches in counseling services or group guidance that are empirically proven to be effective in improving social adjustment in schools. Improved social adjustment should take into account the context of academic and non-academic environments. Guidance curriculum services occupy the largest portion in the implementation of guidance and counseling because it is proactive, preventive and related to behavioral development. The main objective in this article describes the impact, the importance of improving student self-adjustment, and prior research on the importance of improving self-adjustment. this article is expected to contribute positively to the development of the character of students, especially for students who have difficulty in adapting to their environment.